Struktur komunitas ikan pada habitat lamun di Teluk Youtefa Jayapura Papua [Fish community structure at seagrass beds habitat in Youtefa Bay Jayapura Papua] - Selvi Tebaiy; Fredinan Yulianda; Ismudi Muchsin (Jurnal Iktiologi Indonesia, 2014)
This study was carried out from August 2012 to January 2013 in Youtefa Bay, Jayapura, Papua. Study aimed to analyze the species composition and fish communities structure in seagrass ecosystems. Fish sampling was conducted by using gill nets and beach seine experiments with swept method. Fishes were caught once in each month during research period, and conducted on day and night time. The result showed of 676 individuals in 79 fish species of 36 families. Scolopsis lineata (14.64%), Apogon ceramensis (9.76%), Parupeneus barberinus (6.80%), Aeliscus strigatus (6.36%), Siganus fuscescens (4.89%), and Siganus canaliculatus (4.29%) were species that found dominantly in all locations during observation time. The number of fish in each site was affected by the percentage of seagrass beds coverage, the higher percentage of seagrass coverage the higher number of fish found. Higher diversity index found in August, October, and January, the ranged between 3.09 and 4.29; while on September, November and December had lower diversity index, the ranged between 2.09-3.05. Transparency, dissolved oxygen, percentage of coverage, pH, temperature, and nitrate were variables that positively correlated to fish abundance. Abstrak Penelitian ini dilaksanakan pada bulan Agustus 2012 sampai Januari 2013 di Teluk Youtefa Jayapura Papua, bertujuan untuk menganalisis komposisi spesies dan struktur komunitas ikan pada ekosistem lamun. Ikan dikoleksi menggunakan jaring insang dan jaring pantai eksperimental dengan metode penyapuan. Pengamatan dilakukan satu kali setiap bulan selama enam bulan dan dilakukan penangkapan pada siang dan malam hari. Penelitian ini berhasil mengumpulkan 676 individu meliputi 79 spesies dari 36 famili. Jenis Scolopsis lineata (14,64%), Apogon ceramensis (9,76%), Parupeneus barberinus (6,80%), Aeliscus strigatus (6,36%), Siganus fuscescens (4,89%) dan Siganus canaliculatus (4,29%) dite-mukan pada semua lokasi dan waktu pengamatan. Jumlah individu ikan di masing-masing lokasi dipengaruhi oleh nilai persentase tutupan lamun, di mana semakin tinggi nilai persentase tutupan lamun ditemukan jumlah individu yang ting-gi. Indeks keanekaragaman (H’) pada bulan Agustus, Oktober dan Januari yaitu (3,09-4,29) lebih tinggi daripada bulan September, November, dan Desember (2,09-3,05). Variabel kecerahan, oksigen terlarut, persentase tutupan, pH, suhu, dan nitrat berkorelasi positif dengan kelimpahan ikan.